2004
DOI: 10.5694/j.1326-5377.2004.tb05991.x
|View full text |Cite
|
Sign up to set email alerts
|

Proton‐pump inhibitor therapy and the development of dysplasia in patients with Barrett's oesophagus

Abstract: Objective: To examine whether proton‐pump inhibitor (PPI) therapy influences the incidence and progression of dysplasia in patients with Barrett's oesophagus. Design and setting: Review of prospective data on patients undergoing surveillance with regular endoscopy and biopsy at a private endoscopy centre in Canberra, ACT, between 1981 and 2001. Patients: 350 patients diagnosed with Barrett's oesophagus. Interventions: PPI therapy was progressively introduced into clinical practice from late 1989. Once begun, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
116
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(124 citation statements)
references
References 27 publications
5
116
0
3
Order By: Relevance
“…20 Systematic information on surveillance of BO was provided in only two studies. 1019 Three studies used record linkage with the pharmacy prescription database for exposure assessment 101120 ; three studies relied on medical record review 192122 and one on patient self-report. 18 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Systematic information on surveillance of BO was provided in only two studies. 1019 Three studies used record linkage with the pharmacy prescription database for exposure assessment 101120 ; three studies relied on medical record review 192122 and one on patient self-report. 18 …”
Section: Resultsmentioning
confidence: 99%
“…Four cohort studies reported the risk of progression to advanced neoplasia (OAC or BO-HGD) 10111922 (with no information on risk of progression to OAC or BO-HGD separately), and one study reported the risk of progression to any grade of neoplasia (OAC or BO-HGD or BO-LGD). 21 Two case–control studies included only patients with OAC as cases.…”
Section: Resultsmentioning
confidence: 99%
“…An Australian cohort study followed 350 patients with Barrett's oesophagus for a median 4.7 years. Patients who received PPI maintenance from the time of diagnosis had a subsequent five- to 20-fold decreased risk for development of dysplasia and cancer 6. A similar study from the US followed 236 patients with Barrett's oesophagus for an average 5 years 7.…”
mentioning
confidence: 98%
“…[6][7][8] Nonsteroidal anti-inflammatory drugs (NSAIDs), aspirin and perhaps proton pump inhibitor use show a negative correlation with the occurrence of oesophageal adenocarcinoma. [9][10][11] The increasing burden of this disease and poor prognosis has stimulated research in the area but molecular and cellular mechanisms responsible for the development of Barrett's oesophagus and its conversion to neoplasia in a subgroup of patients are not fully understood. Predictive factors need to be identified for timing of preventive interventions and for targeted designs for future studies.…”
mentioning
confidence: 99%